COVID-19 in Conflict: The devastating impact of withdrawing humanitarian support on universal health coverage in Yemen - Sameh Al-Awlaqi; Fekri Dureab; Dhekra Annuzaili; N. Al-Dheeb (Elsevier, 2020)
The authors warn that, in the context of Yemen, the closure of humanitarian lifesaving programmes and shifting support toward health security, i.e. to support COVID-19 response, at the expense of primary health care support, will undermine existing health system strengthening efforts, worsen the humanitarian crisis and will accentuate the impact of COVID-19. The authors urge the international community and the Government of Yemen to carefully consider a more comprehensive approach to support Yemen's COVID-19 response while maintaining, and strengthening, essential public health services.